Multifocal arterial disease: clinical implications and management. (July 2020) - Paraskevas, K.I.; Geroulakos, G.; Veith, F.J.; Mikhailidis, D.P.
Abstract : Purpose of review: Vascular disease often affects more than one territory. Atherosclerosis is a global disease affecting multiple organs/systems. Cardiovascular risk factors are associated with an increased risk for the development of arterial disease in all vascular beds but differ in their individual impacts for each vascular bed. We discuss the various options to identify and manage multifocal arterial disease. Recent findings: Coronary artery disease may coexist with carotid artery stenosis, abdominal aortic aneurysms, and/or peripheral artery disease (PAD). Atherosclerotic renal artery stenosis and renal function impairment may complicate PAD. Recent studies have confirmed that patients with multivascular bed disease have higher risk than patients with monovascular disease. In addition to the specific surgical/endovascular therapeutic options available, aggressive medical treatment and vascular disease prevention strategies should be rigorously implemented to best manage the overall atherosclerotic burden. Summary: A holistic approach is essential to reduce the cardiovascular morbidity and mortality rates of vascular patients. Preventive measures should complement surgical/endovascular procedures so as to improve outcomes.